Review of Acangassuini Galileo & Martins, 2001 (Insecta, Coleoptera, Cerambycidae), with description of a new genus and species, and description of two new species in the tribes Methiini Thomson, 1860 and Oemini Lacordaire, 1868 - Nascimento, Francisco E. De L.; Bravo, Freddy (Zootaxa, 2018)
Acangassuini is reviewed. Acangarana gen. nov. is described for A. santossilvai sp. nov. from Brazil. In addition, two species are newly described from Brazil: Methia flavomera sp. nov. (Methiini) and Stenoeme furca sp. nov. (Oemini).